2012
DOI: 10.1093/jpids/pis076
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors for Cytomegalovirus Infections in Adolescent Females

Abstract: Background. Congenital cytomegalovirus (CMV) is a leading cause of disability, including sensorineural hearing loss, developmental delay, and mental retardation. Understanding risk factors for acquisition of CMV infection in adolescent females will help determine vaccine strategies. Methods. Females (12-17 years) were recruited from primary care settings in Cincinnati, Galveston, Houston, and Nashville from June 2006 to July 2010 for a seroepidemiologic study, from which seronegative participants were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…CMV is more common among socially disadvantaged groups and nonwhite minorities [2][3][4][5][6][7][8][9][10][11][12]. We have recently conducted geospatial analyses demonstrating that CMV seropositivity, including among pregnant women, significantly clusters in poor urban neighborhoods with large minority populations in North Carolina [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…CMV is more common among socially disadvantaged groups and nonwhite minorities [2][3][4][5][6][7][8][9][10][11][12]. We have recently conducted geospatial analyses demonstrating that CMV seropositivity, including among pregnant women, significantly clusters in poor urban neighborhoods with large minority populations in North Carolina [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, other studies, such as in Saudi Arabia, failed to show this correlation [35]. These observations, along with those from other countries around the globe [36], indicate that age was a risk factor for CMV infection, especially in transplant patients [37,38]. For instance, a study reported that the risk of death was significantly increased in patients >38 years old, who underwent transplantation with peripheral blood, with an unrelated or mismatched donor, and who developed a CMV infection [39].…”
Section: In Transplantation Recipients In the Mena Regionmentioning
confidence: 50%
“…Immunity induced by wild-type CMV infection affords women a high degree of protection against acquisition of a second CMV infection and protects the fetus from severe postnatal sensorineural deafness and neurologic damage. In nearly every epidemiologic study where measured, contact with a young child younger than 3 years of age is the most important independent predictor for acquisition of CMV 2,4,9. This includes maternal acquisition of CMV during pregnancy and congenital infection 2,18.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most studies reporting an association between CMV infection and sexual activity have not included contact with a young child in the home as an independent variable 1,5,6,8,10,11. Two studies have included both contact with young children and sexual activity as potential risk factors for CMV infection 2,4. After adjusting for contact with a young child, one study found sexual activity was an independent risk factor for CMV infection and the other did not.…”
Section: Discussionmentioning
confidence: 99%